The asymmetric effect of technological innovation on CO2 emissions in South Africa: New evidence from the QARDL approach - Udeagha, Maxwell Chukwudi; Ngepah, Nicholas (Frontiers in Environmental Science, 2022)
The asymmetric impact of technological innovation on CO2 emissions in South Africa from 1960 to 2020 is evaluated in this study. We apply the newly established quantile autoregressive distributed lag (QARDL) methodology to deal with distributional asymmetry based on the location of CO2 emissions within its own distribution. This distinguishes our analysis from earlier works in the following ways. This research, in contrast to other studies, uses the QARDL technique to assess the long-term stability across the quantiles, resulting in a more adaptable econometric analysis than the traditional frameworks. In order to capture the trade share in South Africa's GDP as well as the quantity of trade compared to world trade, we employ a novel measure of trade openness. We find that (i) technological innovation helps to reduce CO2 emissions both in the short term and over the long term; (ii) scale effect worsens CO2 emissions while technique effect enhances it, supporting the existence of an environmental Kuznets curve (EKC) hypothesis; (iii) energy consumption, foreign direct investment, and industrial value-added degrade environmental quality; and (iv) increasing trade openness is glaringly harmful to the environment over the long term, despite being beneficial in the short term; (v) There are long-term, asymmetric linkages between CO2 emissions, scale effect, technique effect, technological innovation, energy use, foreign direct investment, and trade openness; (vi) industrial value-added, scale effect, technique effect, technical innovation, energy usage, foreign direct investment, and trade openness Granger-cause CO2 emissions over the medium, long, and short terms indicates the significance of these variables in determining CO2 emissions. Based on our empirical findings, this study makes the case that South Africa's government and policymakers should take into account the importance of innovative technologies as a sustainable source of advancements in attaining energy security and promoting ecological integrity in the nation.